Malignant melanoma of the middle ear in 58-year-old woman – case report - Jankowski, Andrzej; Szymańska, Anna; Wągrowska-Danilewicz, Małgorzata; Durko, Tomasz (Menopause Review/Przegląd Menopauzalny, 2009)
Mucosal melanoma is a rare malignant tumor – 0.5–2% of all melanomas, which is not included in TNM classification. Among head and neck localisation, it arise most frequently in the nose and paranasal sinuses, oral cavity, nasopharynx and middle ear. According to this untypical place of melanoma, aggressive behavior and nonspecific symptoms the stage of investigation in this cases is usually late. Surgical resection with appropriate margin of normal mucosa in this localization is difficult, so the prognosis is poor. We report a case of primary melanoma of the middle ear in 58-year-old woman admitted to Otolaryngology Department of the Medical University of Łódź. On admission the patient presented left ear tinnitus and hypoacussis with serosanguineous exudate.